Pengaruh Terapi Rendam Kaki Air Hangat Campuran Garam Himalaya terhadap Penurunan Tekanan Darah pada Lansia Hipertensi Tahun 2024 - Evan Rosiska (STIKES Columbia Asia Medan, 2025)
One of the complementary therapy treatments that can be used for independent and natural interventions is foot hydrotherapy (warm water foot soak). Warm water foot soak therapy plus a mixture of salt is useful for blood pressure lowering therapy in hypertension. The purpose of this study was to determine the effect of warm water foot soak therapy with a mixture of salt on lowering blood pressure in elderly hypertensive patients. The type of research is Quasy-experiment using one group pretest posttest design. The number of samples was 16 respondents taken using the Purposive Sampling technique. The results of the study showed that the average blood pressure before the warm water foot soak therapy with a mixture of salt was systolic 169.62 mmHg and diastolic 102.25 mmHg. The average blood pressure after the warm water foot soak therapy with a mixture of salt was systolic 143.12 mmHg and diastolic 91.88 mmHg. The results of the statistical test showed that there was an effect of warm water foot soak therapy mixed with salt on reducing blood pressure in elderly hypertensive patients in the Siulak Mukai Health Center Work Area in 2024 (p-value = 0.001).